Nusyuz and Domestic Violence in Indonesia: Reinterpreting Punishment Using the Ma'nâ al-Haml Method - Harwis, Harwis; Djalal, Marini Abdul (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2023)
Tafsir and classical jurisprudence provide three stages of solutions for a nusyûz wife. Stages of advising, separating beds, and hitting. This interpretation of nusyûz and the solution to hitting is not appropriate to the current context, so it is necessary to expand the meaning with a ma'nâ al-haml approach. Ma'nâ al-haml is used by bringing the meaning of a pronunciation to a more relevant meaning in terms of conditions, time, and space. This research uses a qualitative approach in analyzing, explaining, describing, and revealing research results. Research conducted in libraries is the method utilized to gather data. This study looks at how nusyûz solutions are interpreted in traditional tafsir and fiqh literature. It then reinterprets them using the ma'nâ al-haml approach by considering the views of modern ulama.These interpretations are then analyzed for their relevance to the laws in force in Indonesia as conditions, space, and time for understanding the pronunciation of the text using the ma'nâ al-haml approach. This research concludes that nusyûz is not caused by the wife's disobedience but rather by her bad morals or the bad morals of her partner. Nusyuz can not only occur from the wife's side but can also occur from the husband's side. Therefore, with the ma'nâ al-haml approach, you need to introspect yourself when dealing with nusyûz issues before giving signals to your partner. The solution to a nusyûz partner is not by hitting them but by discussing and negotiating to find the best solution.